Rancang Bangun Sistem Pengaman Pintu Menggunakan RFID dan Fingerprint - Faridatul Husniyah; Miftachul Ulum; Kunto Aji Wibisono; Riza Alfita (FORTEI (Forum Pendidikan Tinggi Teknik Elektro Indonesia), 2021)
In storing valuables such as electronics, money, jewelry, data and so on, it must be in a safe place. Because the safe factor is a social need of every human being. One of the triggers for crime such as theft, burglary or others is a lack of security, especially in the home environment. Another cause of security is that the door locking system still uses manual locks, making it less effective. Because the door is an important thing in a room, where we can always go in and out to store or put things. From these problems, a door guard using RFID (Radio Frequency Identification) or a fingerprint is needed to make the door safe from crime. This security system is designed using Arduino uno r3 ATmega 328 as a microcontroller equipped with an component of RFID reader and fingerprint sensor as well as a door lock solenoid to access the door. By scanning a fingerprint or scanning an RFID card, the data will then be processed and matched with data that has been registered or stored in the database to be able to access the door. Based on the results of the research that has been done, the value of fingerprint accuracy from 3 tests is 80,6%. The safety system can work quite well according to the design..